Disturbances-based plan of delineating protected area’s buffer zone: A case study in Masigit Kareumbi Mountain, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sumarga E, Swandhi I, Hairatunnisa, Susilowardani D, Nurrahman AY, Sadida A. 2021. Disturbances-based plan of delineating protected area’s buffer zone: A case study in Masigit Kareumbi Mountain, West Java, Indonesia. Biodiversitas 22: 5115-5122. The harmony between ecosystems and people, particularly those who live around and inside protected areas, is a key factor for the success of ecosystem protection. This subsequently will ensure the maintenance of ecosystem capacity in providing different types of services. Unfortunately, human activities are still commonly linked to different types of disturbances inside protected areas. This study aims to spatially analyze the anthropogenic disturbances inside a protected area, with a case study in Mount Masigit Kareumbi Protected Area, Indonesia. Two types of disturbances, which can be directly and indirectly related to human intervention, are analyzed, i.e., fires and encroachment for agricultural purposes. This study used Maximum Enthropy (MaxEnt) to analyze the risk of forest fire, while the encroachment was analyzed based on a combination of satellite image interpretation and direct field observation. Fire risk modeling performed well with a mean AUC of 0.98, estimating high fire risk (fire probability more than 0.5) distributed in about 109 ha area inside the Mount Masigit Kareumbi Protected Area. This study also identified about 428 ha of forest encroachment inside the protected area. This study further used the spatial information of the disturbances to determine the priority for selecting and designing areas for buffer zone development.
Keywords: conservation area; ecosystem protection; forest fires; forest encroachment; spatial planning